Left atrial appendage (LAA) electrical isolation by Maze‐like catheter substrate modification in presence of LAA‐occluder device: A case report. Issue 10 (3rd July 2020) - Zanchi, Simone; Bianchini, Lorenzo; Bordignon, Stefano; Bologna, Fabrizio; Tohoku, Shota; Chen, Shaojie; Chun, Julian K. R.; Schmidt, Boris
Abstract: Maze‐like linear substrate modification in atrial fibrillation patients nonresponders to pulmonary vein isolation represents a feasible technique to gain left atrial appendage electrical isolation even in the presence of a Watchman occluder device. Abstract : Maze‐like linear substrate modification in atrial fibrillation patients nonresponders to pulmonary vein isolation represents a feasible technique to gain left atrial appendage electrical isolation even in the presence of a Watchman occluder device.